CLINICAL STUDY TO EVALUATE THE EFFICACY OF SHATAVARI IN KARSHYA - Madhumita, Majumder (International Journal of Ayurveda and Pharma Research, 2017)
Purpose: Karshya is a clinical condition that can be correlated with under nutrition in which body gets emaciated gradually. Among the eight socially undesirable physical state mentioned by Charak, Karshya has been categorized under nutritional deficiency. Altered function of Vayu and Agni leads to insufficient production of Rasa Dhatu. Uposhoshan of Rasa Dhatu takes place leading to Dhatu Kshaya chronologically. Hence the patients of Karshya suffers from indigestion, malabsorption, defective metabolism. Meda Dhatu and Mamsa Dhatu Kshaya at microscopical level ultimately express its symptom macroscopically. So, the purpose of my study is to provide an Ayurvedic management and prove the efficacy of Shatavari in the management of Karshya which Valya Vayasthapan.Method: 35 patients were diagnosed as Karshya from O.P.D G.B Ayurvedic college, on the basis of subjective and objective parameters which includes sign and symptoms and Anthropometric measurement respectively. Powder Shatavari was administered to every patient at the dose of 12 gm/day in two divided doses for 3 months. Anthropometric measurement like BMI, MUAC etc are computed before and after treatment.Result: Significant reduction in sign and symptoms was found in almost all patients. Statistical analysis of anthropometric measurement of 35 patients showed highly significant where p value was <0.001.Conclusion: Karshya can be efficiently and effectively managed with Ayurvedic medication and the complication be prevented.